2017
DOI: 10.3389/fpls.2017.01224
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Effects of Acibenzolar-S-Methyl for Improving Heat or Drought Stress in Creeping Bentgrass

Abstract: Acibenzolar-S-methyl (ASM) is a synthetic functional analog of salicylic acid which can induce systemic acquired resistance in plants, but its effects on abiotic stress tolerance is not well known. The objectives of this study were to examine effects of acibenzolar-S-methyl on heat or drought tolerance in creeping bentgrass (Agrostis stolonifera) and to determine major ASM-responsive metabolites and proteins associated with enhanced abiotic stress tolerance. Creeping bentgrass plants (cv. ‘Penncross’) were fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 105 publications
(125 reference statements)
1
21
0
Order By: Relevance
“…It has also been shown that pairwise VOC responses can be asymmetric. For example, VOCs produced by Verticillium longisporum fungi upregulated the metabolic activity of Paenibacillus polymyxa , while the VOCs of P. polymyxa inhibited the cellular metabolism and growth of V. longisporum , but upregulated genes related to stress responses and the production of antimicrobial VOCs ( 46 ). These findings suggest that VOCs could drive and be a result of potential coevolutionary dynamics that warrant further study in the future ( 24 ).…”
Section: Microbial Interactions Within a Population Determine Local Voc Productionmentioning
confidence: 99%
“…It has also been shown that pairwise VOC responses can be asymmetric. For example, VOCs produced by Verticillium longisporum fungi upregulated the metabolic activity of Paenibacillus polymyxa , while the VOCs of P. polymyxa inhibited the cellular metabolism and growth of V. longisporum , but upregulated genes related to stress responses and the production of antimicrobial VOCs ( 46 ). These findings suggest that VOCs could drive and be a result of potential coevolutionary dynamics that warrant further study in the future ( 24 ).…”
Section: Microbial Interactions Within a Population Determine Local Voc Productionmentioning
confidence: 99%
“…Additionally, glutamic acid can also be converted back into α‐ketoglutarate to participate in respiration metabolism (Hertz et al, 2007). Previous research demonstrated that glutamic acid, proline, or 5‐oxoproline accumulation had positive effects on improving heat or drought stress tolerance of creeping bentgrass ( Agrostis stolonifera ) and tall fescue ( F. arundinacea ) (Jespersen et al, 2017; Li et al, 2016; Yang et al, 2014; Yu et al, 2012). Phenylalanine belongs to the aromatic amino acid family in secondary metabolism, which is involved in synthesizing salicylic acid, auxin, and melatonin.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic profiling has identified a large number of amino acids, organic acids, and sugars that are involved in energy metabolism, protein synthesis, and antioxidant metabolism for plant tolerance to heat stress in various plant species, including cool‐season grass species (Jespersen & Huang, 2015; Yu et al, 2012). For example, the accumulation of amino acids, including aspartic acid, glutamic acid, proline, 5‐oxoproline, and valine, has been positively associated with heat or drought stress tolerance in various plant species, such as reported in creeping bentgrass ( Agrostis stolonifera ) and tall fescue ( Festuca arundinacea ) (Jespersen et al, 2017; Li et al, 2016; Yang et al, 2014; Yu et al, 2012). Increased levels of organic acids, such as malic acid, threonic acid, and shikimic acid, have also been found in plants with improved heat tolerance (Du et al, 2011; Jespersen & Huang, 2017; Yu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The most important amino acids significantly and strongly accumulated at different time points under stress revealed by our metabolic analysis were aspartic acid di-O-glucoside and phenylacetyl-L-glutamine. These compounds have been well described as involved in stress response in plants, including hulled barley [37, 51, 52].…”
Section: Discussionmentioning
confidence: 99%